A case study on the application of activity-based costing on the inductor component - Filzah Lina, Mohd Safeiee; Siti Khadijah, M. Saad; Mohd Yazid, Abu (Faculty of Industrial Technology, Universitas Trisakti, 2020)
Traditional cost accounting (TCA) is no longer reflecting the current economic reality due to distorted information about the profitability of their orders, products and customers. A new costing method is required to overcome the shortcoming of TCA in the era of rapidly increasing product complexity and diversification. The aim of this work is to apply the method of activity-based costing (ABC) on the inductor component for better accuracy. The work begins by collecting data at electronic industry located at Pahang, Malaysia and the product selected is inductor component. ABC focuses on the costs inherent in the activity -based products to produce, distribute or support the products concerned. Through the method, the work successfully gathered the time spent by operator to complete the task given. The largest time spent is at workstation 1 with 92.12% while the smallest at workstation 2,7, 8 and 14 with 0.1727% respectively. The highest cost of capacity supplied is drum core winding with epoxy activity with MYR 5,869,250.40 and the amount of material used is assigned as the cost driver. As the demand quantity of the product is increase by 10%, the total cost of production is predicted to be MYR 6,365,159.18 while the product cost per unit is MYR 1.50.